Myofibroblast-derived exosomes enhance macrophages to myofibroblasts transition and kidney fibrosis - Wenqiang Yu; Jinfang Song; Shuangquan Chen; Jiayi Nie; Chujun Zhou; Jiamin Huang; Hua Liang (Renal Failure)
A critical event in the pathogenesis of kidney fibrosis is the transition of macrophages into myofibroblasts (MMT). Exosomes play an important role in crosstalk among cells in the kidney and the development of renal fibrosis. However, the role of myofibroblast-derived exosomes in the process of MMT and renal fibrosis progression remains unknown. Here, we examined the role of myofibroblast-derived exosomes in MMT and kidney fibrogenesis. In vitro, transforming growth factor-β1 stimulated the differentiation of kidney fibroblasts into myofibroblasts and promoted exosome release from myofibroblasts. RAW264.7 cells were treated with exosomes derived from myofibroblasts. We found purified exosomes from myofibroblasts trigger the MMT. By contrast, inhibition of exosome production with GW4869 or exosome depletion from the conditioned media abolished the ability of myofibroblasts to induce MMT. Mice treatment with myofibroblast-derived exosomes (Myo-Exo) exhibited severe fibrotic lesion and more abundant MMT cells in kidneys with folic acid (FA) injury, which was negated by TANK-banding kinase-1 inhibitor. Furthermore, suppression of exosome production reduced collagen deposition, extracellular matrix protein accumulation, and MMT in FA nephropathy. Collectively, Myo-Exo enhances the MMT and kidney fibrosis. Blockade of exosomes mediated myofibroblasts–macrophages communication may provide a novel therapeutic target for kidney fibrosis.